Interpretive Possibilities in Islamic Inheritance Law - Asif Iftikhar (African Journal of Gender and Religion (AJGR))
A response to "A Brief Analysis of the Status of a Transgender Beneficiary for Purposes of an Islamic Will Within the South African Context”